Implementasi Analisis Swot Dalam Strategi Pemasaran Produk Mandiri Tabungan Bisnis - Tamara, Angelica (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The findings this article is marketing strategy especially marketing of the savings that implemented by PT. Bank Mandiri including a several strategy which is take a ball strategy,develop a networking, excellent service and satisfy facility that increasing the customer trusting and satisfaction so that customers did not run from the bank. The result of SWOTanalysis found PT Bank Mandiri have a courages to compete in competitive market. SO (strenght opportunities) including market share, strenghten the cooperation with cooperative , increaseing the relation between muslim scholar, government and entrepreneur. WO (weakness opportunity) is do the take a ball strategy, increasing a loyal customer, and increasing a product quality. ST (streght treaths) take a cooperation with another banks to set a marketing target and increasing a service quality. WT (weakness treaths) is increasing the promotion with a several media and set an effectiveness and efficiency marketing strategy.Keywords: SWOT, Marketing Strategy, Mandiri Business Savings